2021
DOI: 10.1002/spe.3009
|View full text |Cite
|
Sign up to set email alerts
|

Software effort estimation accuracy prediction of machine learning techniques: A systematic performance evaluation

Abstract: Software effort estimation accuracy is a key factor in effective planning, controlling, and delivering a successful software project within budget and schedule.The overestimation and underestimation both are the key challenges for future software development, henceforth there is a continuous need for accuracy in software effort estimation. The researchers and practitioners are striving to identify which machine learning estimation technique gives more accurate results based on evaluation measures, datasets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…In order to evaluate the classification effects of the trained classification model, some evaluation indexes are needed to measure it. The author mainly selected the classification accuracy [ 44 ], precision [ 45 ], recall [ 46 ], and F value [ 47 ] to evaluate the classification effects achieved by the classification model on the data set.…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the classification effects of the trained classification model, some evaluation indexes are needed to measure it. The author mainly selected the classification accuracy [ 44 ], precision [ 45 ], recall [ 46 ], and F value [ 47 ] to evaluate the classification effects achieved by the classification model on the data set.…”
Section: Methodsmentioning
confidence: 99%
“…Neural network-based models are a relatively new addition to the arsenal of machine learning techniques [6]. They are utilized in software effort estimating because they learn faster and more efficiently with more accurate results [23], [32].…”
Section: Related Workmentioning
confidence: 99%
“…The final results suggested that the ensemble model improved the accuracy of estimation. Mahmood et al 41 investigated the machine learning techniques which were implemented in the construction of ensemble effort estimation techniques. Their results suggested that the machine learning ensemble techniques perform better than solo techniques.…”
Section: Literature Reviewmentioning
confidence: 99%